Long‐term evolution of the natural isolate of Escherichia coli 536 in the mouse gut colonized after maternal transmission reveals convergence in the constitutive expression of the lactose operon. Issue 19 (23rd September 2019) - Ghalayini, Mohamed; Magnan, Melanie; Dion, Sara; Zatout, Ouassila; Bourguignon, Lucie; Tenaillon, Olivier; Lescat, Mathilde
Abstract: In vitro experimental evolution has taught us many lessons on the molecular bases of adaptation. To move towards more natural settings, evolution in the mice gut has been successfully performed. Yet, these experiments suffered from the use of laboratory strains as well as the use of axenic or streptomycin‐treated mice to maintain the inoculated strains. To circumvent these limitations, we conducted a one‐year experimental evolution in vivo using a natural isolate of E. coli, strain 536, in conditions mimicking as much as possible natural environment with mother‐to‐offspring microbiota transmission. Mice were then distributed in 24 independent cages and separated into two different diets: a regular one (chow diet, CD) and high‐fat and high‐sugar one (Western Diet, WD). Genome sequences revealed an early and rapid selection during the breastfeeding period that selected the constitutive expression of the well‐characterized lactose operon. E. coli was lost significantly more in CD than WD; however, we could not detect any genomic signature of selection, nor any diet specificities during the later part of the experiments. The apparently neutral evolution presumably due to low population size maintained nevertheless at high frequency the early selected mutations affecting lactose regulation. The rapid loss of lactose operon regulation challenges the idea that plastic gene expression is both optimal and stable in the wild.